Mobile-Assisted Interactive Multimedia in Language Literacy Class: Exploring Primary School Teachers’ Voices - Choiroh Nurussyifa; Akbar Al Masjid; Zainnur Wijayanto (Wahana Pendidikan, 2026)
In primary education, language literacy has become a central focus particularly as learners are increasingly exposed to digital-based learning environments. However, the integration of interactive multimedia to support literacy development remains under-explored, especially in contexts where teachers face pedagogical, technological, and infrastructural challenges. This study aims to describe teachers’ perceptions regarding the use of mobile-based interactive multimedia in language literacy class in primary schools. This qualitative case study employed close-ended questionnaires and semi-structured interviews with forty primary school teachers from diverse teaching backgrounds. Findings revealed that effective digital multimedia should relate to appearance and design, interactivity, ease of use, audio-visual quality, and alignment of media with learning objectives. It was also found that teachers experience difficulties in fostering literacy due to poor integration of literacy learning within the subject content, use of varied learning media, interactive literacy learning, and innovation in literacy instruction. Findings showed that teachers expect digital interactive platforms which had high interactivity, built-in scaffolding, meaningful feedback, and contextualized content. The study highlights the need for more systematic professional development, inclusive multimedia design, and collaborative approaches in supporting teachers to optimize digital interactive multimedia for literacy instruction.